El rincón de construcción para el desarrollo de la inteligencia espacial de niños y niñas de 4 a 5 años de edad, de la Escuela de Educación Básica Demetrio Aguilera Malta, recinto Illuví, parroquia Guanujo, cantón Guaranda, provincia Bolívar, periodo 2022 - Hurtado Pazmiño, Maritza Paola (2023)
The Initial Education curriculum prioritizes the development of skills and/or skills with performance criteria based on learning environments in which children are in direct contact with spaces that simulate everyday scenarios, one of them, the one that enhances an essential ability in children is the topic that is broken down in this project, for this purpose it is proposed as a general objective: Implement the construction corner for the development of spatial intelligence of boys and girls from 4 to 5 years of age from the Demetrio Aguilera Malta Basic Education School; In order to meet the objective, a methodology attached to the inductive, deductive process is developed; with the first, it starts from reality, to generalize its results; with the deduction it goes the other way; of theories or general positions, it is possible to establish particularities of children of 4 and 5 years based on the corner of construction and development of spatial intelligence. For its part, consistent with the types, the descriptive method is used to characterize the institutional reality; action research is used; analysis, synthesis as methods; The results obtained make it possible to show that the performance results, framed in the achievement indicators, specifically with regard to spatial intelligence, are improved with the presence and work in the construction corner; contributes adequately to the contextualized solution of the problem.